TASTE MASKING IN ORAL DOSAGE FORMS: EXPLORING CONVENTIONAL AND NANOTECHNOLOGY-BASED APPROACHES (The Research of Medical Science Review, 2025)
Patient compliance is essential for successful pharmacotherapy, and oral medications that taste bad, especially to young and elderly patients, are often the reason for non-compliance. Taste masking is therefore crucial for improving patient adherence and therapeutic outcomes. This review looks at a variety of taste-masking techniques, including both well-known and innovative technologies based on nanotechnology. Nanotechnology offers promising alternatives to traditional methods such as coating, granulation, microencapsulation, and the addition of sweeteners, which have disadvantages such as uneven masking and potential effects on medication efficacy. These methods include the use of nanocarriers, liposomes, nanoparticles, and nano emulsions. These innovative techniques can successfully mask undesirable flavors, enhance the delivery of oral medications, and ultimately improve patient compliance and quality of life